Perbaikan Tata Letak Zona Lining Menggunakan Metode Activity Relationship Chart (ARC) di PT BSS - Krisdian, Aris; Suwarni, Putri Endah; Septiani, Riana; Sundari, Susanti (Fakultas Teknik Universitas Tulang Bawang, 2025)
PT. BSS is a company engaged in the processing of spices using a make-to-order production system. The main problem faced by the company is the unstructured flow of material movement between the Non-Hygiene, Low Hygiene, High Hygiene, and Disposal zones, which results in inefficiencies in both time and space utilization. Through the ARC approach, supported by the From-To Chart, Activity Relationship Diagram (ARD), Activity Template Block Diagram (ATBD), and Area Allocation Diagram (AAD), an analysis of the inter-activity relationships and a redesign of the production layout were carried out. The results of the study show that the new layout successfully reduced the material handling distance from 600 meters to 430 meters, representing a decrease of 28.3%. In addition, the storage capacity in the Non-Hygiene zone increased from 40 to 63 pallets (an increase of 57.5%) without requiring any building expansion. The new layout also accelerated the average material transfer time by 10–15 minutes per shift and reduced the potential for cross-contamination by up to 70% through stricter separation of zones in accordance with hygiene standards. Keywords: Activity Relationship Chart (ARC), Facility layout, production efficiency, 5R, zone lining